Navigating the digital shift: a cross-sectional study on social media usage, academic performance, and family dynamics among university students in Palestine during COVID-19 quarantine - Deeb, Salahaldeen; Alfrookh, Mohammad Harbi; Zurayqi, Anas Khaled; Dweik, Yasmina Farouq; Dabash, Mohammed Rami; Deeb, Nouraldeen; Amro, Alhareth M. (Frontiers in Education, 2025)
This study explores the profound impact of COVID-19 quarantine on social media usage among university students in the West Bank, revealing a dramatic surge in engagement driven by the shift to remote learning and the need for digital socialization. With motivations for entertainment (52%) and social communication (28%) dominating, students reported increased social media use, which coincided with heightened study hours, reflecting its dual role as both a tool for academic adaptation and a potential distraction. Quarantine conditions also fostered stronger family relationships, with students spending more time with their families, yet satisfaction with academic performance and daily achievements remained low, highlighting the challenges of balancing increased digital engagement with productivity. This research underscores the complex interplay between social media, academic performance, and social dynamics during an unprecedented period of global disruption, offering valuable insights for educators, policymakers, and mental health professionals aiming to optimize social media’s role in academic and personal development.